Building actor relationships and alliances for complex problem solving in spatial planning: The test planning method. Test planning as a means of solving complex problems in spatial planning. - Scholl, Bernd (Routledge, 2017)
In order to explore, clarify and solve complex challenges in spatial development, effective cooperation between spatially significant actors is essential. To this end, formal methods and instruments have been in place since the early 1970s. These are based on legal principles and existing established organizations. However, in recent decades it has become clear that this formal repertoire is, in most cases, in-sufficient. The sheer complexity of the associated challenges presents formal methods - and the actors involved - with a serious challenge. A key weck point is most notably the series of connected procedures necessary when trying to find a solution and the inertia of hierarchically structured organizations when faced with collaboration. These methods are referred to in die industry as "consecutive methods". As a way of supplementing formal processes, recent decades have seen the appearance of informal procedures as a result. These are typically characterized by direct dialogue between competing problem-solving ideas, along with constructive criticism, within the context of processes that are structured according to a definite timeframe and based on particular principles. Such processes are typically referred to as "simultaneous methods". These allow for versatile operational implementation when the appropriate method is used. In German-speaking countries, and in Switzer-land in particular, one such method has taken root: the test planning method. The following article focuses on this method, its principles and its underlying philosophy, all of which are illustrated by means of case studies. The article concludes with an outlook in terms of future prospects.
Keywords: Planung; Theorie; Stadtplanung; Planungsprozess; Planungstheorie; Organisationsform; Kooperation; Transformationsprozess; Planungsansatz; Informelle Planung; Problemlösung; Akteur; Gleichzeitigkeit; Testplanung; Fallbeispiel